TRADISI PANTANG LARANG MEMBANGUN KESADARAN PEDULI LINGKUNGAN MUSLIM-MELAYU KOTA PONTIANAK - Putri, Pratiwi Amalia (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2024)
The aim of this research is to demonstrate that taboos are a part of local wisdom that can serve as a learning resource for the people of Pontianak, particularly in fostering environmental awareness. Currently, the world is facing a climate crisis, prompting UNESCO to launch the climate action program among 17 other initiatives, indicating that the climate crisis is a significant issue requiring action from various parties. To conduct this study, the researcher employed a qualitative-descriptive method, collecting data through interviews and literature review. After gathering the data, the researcher analyzed it through data condensation, data presentation, and drawing conclusions. The results indicate that taboos have the potential to be a learning resource for the people of Pontianak regarding the environment, as they contain prohibitions relevant to environmental sustainability through their implicit meanings.